Thai cinema: the complete guide - Ainslie, Mary J.; Ancuta, Katarzyna ("I.B. Tauris Film & Media Studies 2018, 2019)
"One of the fastest growing and most internationally renowned cinemas in Southeast Asia is that of Thailand. In the first ever book devoted solely to this major centre of creative filmmaking, experts on contemporary and historic Thai film provide a timely overview and discussion of key films, directors and current movements in the region in a comprehensive encyclopaedia format. What many critics, analysts and scholars have retrospectively christened `New Thai Cinema' began to take shape in the late 1990s when national film moved away from its position as lower-class and provincial entertainment and became a firm fixture in Bangkok multiplexes and festivals worldwide. This book will provide information on the influential figures behind the films - up to and succeeding the 1997 watershed film Dang Bireley's and Young Gangsters that began the breakaway movement - as well as detailing and explaining the traditions of popular and art-house genres specific to Thailand. Featuring contributions on Thai visionaries such as Apichatpong Weerasethakul and Wisit Sasanatieng and providing rare insight into early Thai cinema, this is an essential scholarly guide to a vibrant aspect of Southeast Asian cinema - its history, industry and aesthetic trends - for scholars and students alike."--